ENHANCING STUDENTSâ€™ READING ABILITY IN INTERMEDIATE READING CLASS THROUGH SQ4R (A CLASSROOM ACTION RESEARCH) - Ita Permatasari; Titik Rahayu; Eda Maaliah (Universitas Katolik Widya Mandala Surabaya, 2020)
Abstract Based on the result of preliminary study, it was found that studentsâ€™ reading ability of second graders ofEnglish Department was considered low. This condition can be seen as the result of the pre-test in whichmost of the students scored lower than 68, since the institution in which this research took place gradedthe range score of 68 as â€œGoodâ€. Therefore, an alternative method in reading activity was introducednamely SQ4R. SQ4R is a reading strategy which consists of 6 steps; survey, question, read, recite,relate, and review. There were 27 students involved in this research. The data were gathered from theresult of test in each Cycle, observation and FGD. The result of the research which was conducted intwo Cycle shows that there was significance improvement of studentsâ€™ reading score in which 23 out of27 students (85%) of the students could score 68. Â Keywords: reading, reading skill, SQ4R